Molecular Signature of Pseudomonas aeruginosa with Simultaneous Nanomolar Detection of Quorum Sensing Signaling Molecules at a Boron-Doped Diamond Electrode - Buzid, A.; Shang, F.; Reen, F.; Muimhneacháin, E.; Clarke, S.; Zhou, L.; Luong, J.; O'Gara, Fergal; McGlacken, G.; Glennon, J. (Nature Publishing Group, 2016)
Electroanalysis was performed using a boron-doped diamond (BDD) electrode for the simultaneous detection of 2-heptyl-3-hydroxy-4-quinolone (PQS), 2-heptyl-4-hydroxyquinoline (HHQ) and pyocyanin (PYO). PQS and its precursor HHQ are two important signal molecules produced by Pseudomonas aeruginosa, while PYO is a redox active toxin involved in virulence and pathogenesis. This Gram-negative and opportunistic human pathogen is associated with a hospital-acquired infection particularly in patients with compromised immunity and is the primary cause of morbidity and mortality in cystic fibrosis (CF) patients. Early detection is crucial in the clinical management of this pathogen, with established infections entering a biofilm lifestyle that is refractory to conventional antibiotic therapies. Herein, a detection procedure was optimized and proven for the simultaneous detection of PYO, HHQ and PQS in standard mixtures, biological samples, and P. aeruginosa spiked CF sputum samples with remarkable sensitivity, down to nanomolar levels. Differential pulse voltammetry (DPV) scans were also applicable for monitoring the production of PYO, HHQ and PQS in P. aeruginosa PA14 over 8 h of cultivation. The simultaneous detection of these three compounds represents a molecular signature specific to this pathogen.